Überlegungen zu Heinrich Schäfers Von ägyptischer Kunst und zu Hedwig Fechheimers Plastik der Aegypter - Peuckert, Sylvia (Zeitschrift für ägyptische Sprache und Altertumskunde, 2017)
Hedwig Fechheimer’s Plastik der Aegypter and the first edition of Heinrich Schäfer’s Von ägyptischer Kunst were published respectively directly before and after the First World War. In these books, two very different theories about Egyptian art were presented, the intellectual premises of which are explored in this article. Fechheimer’s perception of Cubism in France serves as one starting point and Schäfer’s numerous quotations from German literature, particularly from Goethe’s works, as a second. This study leads to Schäfer’s connection to the Fichte-Gesellschaft von 1914 , his proximity to the journal Deutsches Volkstum , and finally to the question of his relationship to National Socialism. The positions of the two authors to the evolutionistic perception of art during this period are an important point of comparison.